Post-supereruption recovery at Toba Caldera - Mucek, Adonara E.; Danišik, Martin; Schmitt, Axel Karl (Nature Communications, 2017)
Toba Caldera in Indonesia had one of the largest volcanic eruptions over the last 100 kyr and has since undergone periods of resurgence. Here, the authors present zircon and sediment age data showing resurgence started after the climactic eruption and lasted until 2.7 ka,…